Insights into an undescribed high‐elevation lake (6, 170 m a.s.l.) on Volcán Llullaillaco: A physical and microbiological view. Issue 8 (14th May 2021) - Aran, Pablo; Aguilar, Pablo; Bowen, Thomas; Farson, Matthew; Tapia, Joseline; Vimercati, Lara; Darcy, John L.; Solon, Adam J.; Porazinska, Dorota; Schmidt, Steven K.; Dorador, Cristina
Abstract: High elevation lakes are extreme ecosystems and serve as sentinels of various global changes. An expedition to Volcán Llullaillaco in 1996 discovered an unstudied high‐elevation lake (6, 170 m a.s.l.) that probably was formed as a result of the past eruptive events or climatic processes such as glacial retreat in the lake basin. This article describes an initial physical characterization of the lake and its microbial communities derived from two sampling expeditions in 2013 and 2016. The microbial community in the lake, with an area between 1.2 and 1.4 ha and a depth of 6.8 m, was dominated by Proteobacteria, Actinobacteria and Haloarchaea. In addition, 26 bacterial isolates were identified within the genera Subtercola, Xylophilus, Rhodanobacter, Mesorhizobium and Pseudomonas . Lago Llullaillaco is one of the highest recorded lakes in the world, and this study highlights the unique microbial diversity of this aquatic ecosystem and the importance of its preservation to understand the complex biological processes under polyextreme conditions.